Cerebral microbleeds in geriatric patients with non-valvular atrial fibrillation - M. S. Chernyaeva; A. A. Pogodina; E. A. Prokhorova; E. A. Moiseeva; M. A. Rozhkova; M. A. Trifonov; L. A. Egorova; O. M. Maslennikova; N. V. Lomakin; D. A. Sychev (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence and structure of cerebral microbleeds (CMBs) in patients ≥80 years old with non-valvular atrial fibrillation in real-world practice.Material and methods. Eighty patients were examined (median age 83 (81; 86) years, 72,5% women). All patients underwent brain magnetic resonance imaging using a MAGNETOM Skyra system 3 Tesla (Siemens) during the initial examination and again one year later.Results. During the initial examination, the detection rate of CMBs was 48,8% and did not differ significantly depending on the direct oral anticoagulant taken (p=0,738). There were 161 CMBs in 39 patients (an average of 4,1±3,6 CMBs per patient). During the repeated examination, newly detected CMBs were in 21,6% of patients. In the initial examination, mixed location of CMBs prevailed (43,6%), mainly in the frontal lobe (25,5%), while in reexamination, lobar location (54,5%) and also mainly in the frontal lobe (43,5%).Conclusion. The high detection rate of CMBs in patients ≥80 years with non-valvular atrial fibrillation, both at the initial examination and after one year, especially in the lobar location, indicates a high risk of intracranial hemorrhage. Its prevention requires a multidisciplinary approach to the management of such patients.